Epstein-Barr Virus Infection in Transplant Recipients: Sumary of a Workshop on Surveillance, Prevention and Treatment. (1st April 2002) - Allen, Upton; Alfieri, Caroline; Preiksaitis, Jutta; Humar, Atul; Moore, Dorothy; Tapiero, Bruce; Tellier, Raymond; Green, Michael; Davies, Dele; Hébert, Diane; Weitzman, Sheila; Petric, Martin; et al.
Abstract : Diseases caused by the Epstein-Barr virus are of great significance among organ transplant recipients. One of these diseases, post-transplant lymphoproliferative disease, is a major complication among organ transplant recipients. Management of this entity is problematic due to the difficulties with laboratory surveillance, diagnosis, prevention and treatment. A group of Canadian and American experts was assembled to discuss these aspects of Epstein-Barr virus diseases in Canadian organ transplant recipients. This report summarizes the relevant background literature and levels of evidence in relation to the outcomes of the deliberations and recommendations by the expert panel.